The ghosts of Eden Park : the bootleg king, the women who pursued him, and the murder that shocked jazz- age America - Abbott, Karen, 1973- (Crown, 2019)
"The epic true crime story of bootlegger George Remus and the murder that shocked the nation, from the New York Times bestselling author of Sin in the Second City and Liar, Temptress, Soldier, Spy. In the early days of Prohibition, long before Al Capone became a household name, a German immigrant named George Remus quits practicing law and starts trafficking whiskey. Within two years he's a multi-millionaire. The press calls him "King of the Bootleggers," writing breathless stories about the Gatsby-esque events he and his glamorous second wife, Imogene, host at their Cincinnati mansion, with party favors ranging from diamond jewelry for the men to brand-new Pontiacs for the women. By the summer of 1921, Remus owns 35 percent of all the liquor in the United States. Pioneering prosecutor Mabel Walker Willebrandt is determined to bring him down. Willebrandt's bosses at the U.S. Attorney's office hired her right out of law school, assuming she'd pose no real threat to the cozy relationship they maintain with Remus. Eager to prove them wrong, she dispatches her best investigator, Franklin Dodge, to look into his empire. It's a decision with deadly consequences: with Remus behind bars, Franklin and Imogene begin an affair and plot to ruin him, sparking a bitter feud that soon reaches the highest levels of government--and that can only end in murder. Combining deep historical research with novelistic flair, THE GHOSTS OF EDEN PARK is the unforgettable, stranger-than-fiction story of a rags-to-riches entrepreneur and a long-forgotten heroine, of the excesses and absurdities of the Jazz Age, and of the infinite human capacity to deceive"--